Rancang Bangun Intensitymeter Berbasis MEMS Dengan Algoritma Pendeteksi Kejadian STA/LTA dan Sistem Peringatan Multi-Saluran - Aziz Rawana; Benyamin Heryanto Rusanto; Edward Trihadi; Nardi Nardi (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
Indonesia is an earthquake-prone country due to its location at the convergence of three major tectonic plates. To support disaster mitigation, a reliable and affordable monitoring system is required. This study presents a low-cost intensitymeter using a MEMS WT61C sensor with the STA/LTA detection algorithm, Raspberry Pi 4 for processing, and a Ublox Neo-M8N GNSS module for time and location synchronization. The system supports online and offline modes with a store-and-forward mechanism and delivers alerts via buzzer, SMS, and Telegram. The WT61C was configured with 20 Hz bandwidth and 100 Hz sampling rate. Tests showed the device detected local earthquakes, calculated Peak Ground Acceleration (PGA), and estimated Modified Mercalli Intensity (MMI). In simulations of the Lombok 2018 earthquake (M7.0), it produced PGA values of 0.5704 g (23.3% error) and 0.7495 g (0.8% error) against the reference 0.744 g, both consistent with MMI VIII. SMS was sent serially with 5–7 s latency, while Telegram worked in real time. Validation was limited to a simulator with one dataset, without diverse soil or magnitude scenarios. In conclusion, the system provides an effective, low-cost solution for earthquake intensity monitoring and has potential for early warning applications.